Pengembangan Bandar Udara Fatmawati Dalam Mendukung Visit Wonderful Bengkulu 2020 - Sitti Subekti (WARTA ARDHIA, 2018)
The Development of Fatmawati Airport in Supporting Visit Wonderful Bengkulu 2020: This research is conducted with regard to the strategy of Fatmawati Airport Bengkulu development in supporting Visit Bengkulu 2020. The purpose of this research is not only related to the development strategy of Fatmawati Airport Bengkulu in supporting Visit Bengkulu 2020 but also to determine the accessibility of the airport to the tourism sites. Primary and secondary data was used in this study. Data analysis was exercised using SWOT method and qualitative descriptive. The results of research indicate four Strength Opportunity (SO) strategies for the development of Fatmawati Airport Bengkulu, namely the need for increased investment cooperation and partnership with other agencies as the impact of the establishment of Fatmawati Airport Bengkulu as a BLU, airport development to serve the increase of air transport through the operation of wide body aircraft, increased commitment of excellent service by Fatmawati Airport Bengkulu with the support from the Ministry of Transportation and Local Government in the construction of airport facilities and increased accessibility from and to the tourist attraction sites due to its strategic location in the city center while has also become the main node of transportation, and availability of connecting transportation modes to support the accessibility to and from the airport among others two BRT corridors of “Trans Rafflesia” which is planned to cross the tourism sites in Bengkulu City where corridor 1 will getting passengers to Panjang Beach and Marlborought Port and corridor 2 to Dendam Lake. Penelitian ini dilakukan terkait dengan strategi pengembangan Bandar Udara Fatmawati Bengkulu dalam mendukung program Visit Wonderful Bengkulu 2020. Tujuan penelitian ini adalah untuk mengetahui strategi pengembangan Bandar Udara Fatmawati Bengkulu dalam mendukungan visit Bengkulu 2020, dan untuk mengetahui ketersediaan aksesibilitas (moda lanjutan) dari bandar udara Fatmawati Bengkulu ke obyek wisata dan sebaliknya. Penelitian menggunakan data primer dan sekunder. Analisis data dengan metode analisis SWOT dan deskriptif kualitatif. Hasil penelitian menunjukkan terdapat 4 (empat) Strength Opportunity (SO) strategi dalam pengembangan Bandar Udara Fatmawati Bengkulu, yaitu perlunya peningkatan kerjasama investasi dan kemitraan dengan instansi lain sebagai dampak dari penetapan Bandar udara Fatmawati sebagai BLU, pengembangan bandar udara untuk dapat melayani peningkatan angkutan udara melalui pengoperasian pesawat berbadan besar (wide body), peningkatankomitmen pelayanan prima bandar udara Fatmawati dengan dukungan Kementerian Perhubungan dan Pemerintah Daerah dalam pembangunan fasilitas bandar udara dan peningkatan aksesibilitas dari dan ke objek wisata karena letak bandar udara yang strategis di pusat kota dan menjadi simpul utama transportasi. Ketersedian moda lanjutan untuk mendukung aksesibilitas dari dan ke bandar udara antara lain 2 (dua) koridor BRT “Trans Rafflesia” yang direncanakan akan melintasi obyek wisata di Kota Bengkulu yaitu koridor 1 melewati pantai Panjang dan benteng Marlborough serta koridor 2 yang melewati obyek wisata danau Dendam.